PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN GUCI BAKERY & CAKE DI KABUPATEN TEGAL - Ayu Cahyani Putri, 15.05.51.0255; Soliha, Euis (Students' Journal of Economic and Management, 2019)
This study aims to analyze the effect of product quality, price perception, and store atmosphere on consumer purchasing decisions of Guci Bakery & Cake in Tegal Regency. This study uses a survey method with a questionnaire as a data collection tool. The population in this study were all consumers who bought Guci Bakery & Cake products in Tegal Regency. The sample in this study were 100 respondents with purposive sampling as a sampling technique. The data analysis technique in this study used multiple linear regression analysis. The result showed that product quality had a positive and significant effect on purchasing decisions, price perception had a positive and significant effect on purchasing decisions, and store atmosphere had a positive and significant effect on purchasing decisions.